Transformasi Pekerjaan di Era Digital: Analisis Dampak Teknologi Pada Pasar Kerja Modern - Munawati Munawati; Wahyuddin Wahyuddin; Nur Riswandi Marsuki (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The transformation of work in the digital era has had a major impact on the modern job market. Technology has changed the way work is done, with automation, artificial intelligence and digitalization playing a key role. This results in a change in the skills required, with an emphasis on technology understanding, problem solving, and creativity. This research aims to examine the analysis of the impact of technology on the modern job market. The type of research used is using qualitative methods with a library research approach, and descriptive qualitative. The results of this research show that there are challenges, including unequal access to technology, which can increase social and economic disparities. Additionally, concerns about data security, privacy and the psychological impact of digital work have also emerged.